Role of quantitative p16INK4A mRNA assay and digital reading of p16INK4A immunostained sections in diagnosis of cervical intraepithelial neoplasia. Issue 4 (1st June 2017) - Vasiljević, Nataša; Carter, Paul D.; Reuter, Caroline; Warman, Rhian; Brentnall, Adam R.; Carton, James R.; Cuzick, Jack; Lorincz, Attila T.
Abstract : Visual interpretation of cervical biopsies is subjective and variable, generally showing fair to moderate inter‐reader agreement in distinguishing high from low grade cervical intraepithelial neoplasia (CIN). We investigated the performance of two objective p16 quantitative tests in comparison with visual assessment: ( i ) p16‐mRNA assay and ( ii ) digital analysis of sections stained for p16 protein. The primary analysis considered 232 high‐risk human papilloma virus positive (HPV+) samples from diagnostic cervical specimens. A p16 RT‐qPCR (p16‐mRNA assay) was run on mRNA extracted from formalin‐fixed paraffin‐embedded sections. Two p16 immunohistochemistry (IHC) readings, a visual read by a histopathologist (Visual IHC) and a digital read of a high‐resolution scan (Digital IHC), were done on adjacent sections. The worst reviewed CIN grade (agreed by at least two histopathologists) from up to two biopsies and a loop excision was taken, with CIN2/3 as the primary endpoint. Visual IHC attained a specificity of 70% (95%CI 61–77) for 85% (95%CI 77–91%) sensitivity. The four‐point Visual IHC staining area under the curve (AUC) was 0.77 (95%CI 0.71–0.82), compared with 0.71 (95%CI 0.64–0.77) for p16‐mRNA and 0.67 (95%CI 0.60–0.74) for Digital IHC. Spearman rank‐order correlations were: visual to p16‐mRNA 0.41, visual to digital 0.49 and p16‐mRNA to digital: 0.22. The addition of p16‐mRNA assay to visual reading of p16 IHC improved the AUC from 0.77 to 0.84 ( p  = 0.0049). p16‐mRNA testing may be complementary to visual IHC p16 staining for a more accurate diagnosis of CIN, or perhaps a substitute in locations with a lack of skilled pathologists. Abstract : What's new? Visual examination of cervical tissue obtained by biopsy provides information on morphological changes associated with human papillomavirus (HPV) infection and transformation to precancerous cervical intraepithelial neoplasia 2/3 (CIN2/3). The accuracy of CIN2/3 diagnosis by visual interpretation, however, could be improved through the use of complementary objective tests. This study describes two such tests: quantitative p16 mRNA analysis and digital analysis of immunohistochemical p16‐protein staining. CIN2/3 diagnostic accuracy benefitted especially from the addition of p16‐mRNA testing. Both new approaches could prove useful in locations lacking trained pathologists and could help avoid overtreatment in HPV‐positive women, many of whom recover spontaneously.